Bilateral hamstring origin calcification: rare presentation of Gitelman syndrome. Issue 1 (7th January 2020) - Mohan, Rahul; Dhotare, Satish Vinayakrao; Unnikrishnan, P Nithin; Jakaraddi, Chetan
Abstract : This case report is the first case to our knowledge of intratendinous or peritendinous calcification reported in Gitelman syndrome (GS) patients. GS represents the clinical manifestations of inactivation of the Slc12a3 genes encoding the thiazide-sensitive sodium chloride cotransporter and the Trpm6-Mg genes encoding the magnesium transporters in the distal convoluted tubule. Hence, the biochemical findings resemble those with thiazide diuretics such as hypokalaemia, hypomagnesaemia, hypocalciuria, metabolic alkalosis and low normal blood pressure. Serum calcium and phosphate levels are usually unaffected in GS unless associated with hyperparathyroidism or other hypercalcaemic aetiologies. We report a 69-year-old male patient with a history of GS who presented with bilateral ischial tuberosity tenderness. Further investigations confirmed the calcification of bilateral hamstring origin. Chondrocalcinosis is a known association of GS; however, extra-articular calcification is rare. Literature review illustrates sclerochoroidal calcification as the only reported soft tissue calcification apart from chondrocalcinosis.